2014
DOI: 10.1080/13557858.2014.895976
|View full text |Cite
|
Sign up to set email alerts
|

Treatment delay for Māori women with breast cancer in New Zealand

Abstract: This study shows that significant inequities in timely access to surgical treatment for breast cancer exist in NZ, with Māori and Pacific women having to wait longer to access treatment than NZ European women. Overall, a high proportion of women did not receive surgical treatment for breast cancer within the guideline limit of 31 days. Urgent steps are needed to reduce ethnic inequities in timely access to breast cancer treatment, and to shorten treatment delays in the public sector for all women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 31 publications
3
34
0
2
Order By: Relevance
“…Além disso, outro estudo constatou que mulheres com mais de 80 anos iniciavam tratamento mais precocemente que mulheres mais jovens 28 . Na Nova Zelândia, um estudo mostrou que o atraso foi maior para as mulheres em faixa etária menor que 50 anos e maior que 70 anos 32 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Além disso, outro estudo constatou que mulheres com mais de 80 anos iniciavam tratamento mais precocemente que mulheres mais jovens 28 . Na Nova Zelândia, um estudo mostrou que o atraso foi maior para as mulheres em faixa etária menor que 50 anos e maior que 70 anos 32 .…”
Section: Resultsunclassified
“…Esse estudo concluiu que em grupos minoritários o atraso é maior do que em mulheres brancas, e que a morosidade na realização do diagnóstico e do tratamento das mulheres negras norte-americanas demonstrou a fragilidade do sistema de saúde dos Estados Unidos em prestar assistência adequada a esse grupo, desde a detecção do câncer até o tratamento paliativo 28 . Autores neozelandeses corroboraram a afirmativa de que há disparidade no acesso aos serviços de saúde para grupos minoritários, concluindo que as populações nativas do país compostas por mulheres Maori (37,1 dias) e do Pacífico (42,8 dias) foram submetidas à cirurgia primária mais tardiamente que as mulheres de origem europeia (30,4 dias) 32 . Resultado semelhante foi compartilhado por outros pesquisadores 18,21,27,29,34 .…”
Section: Resultsunclassified
“…Although publicly funded screening and treatment services are available nationwide in New Zealand, there is some evidence of differential access or quality of care by screen-detection status and ethnic group. Surgery delays have been reported as more common in non-BSA diagnosed women and among Māori, and surgery delay in the public sector was also found to be more likely than in the private sector (Seneviratne et al , 2015; Lawrenson et al , 2016). Māori women have also been observed as less likely to have radiotherapy and/or adhere to long-term adjuvant endocrine therapy, and more likely to have a mastectomy, than non-Māori women (Lawrenson et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A study of delays to breast cancer surgical treatment in the Waikato region found the main driver for inequity in timeliness to surgery was greater access to private treatment among non-M aori women (Seneviratne et al 2015). In this study, among M aori women in the screening age group who were treated in the public sector, those who were diagnosed through BSA had shorter mean wait times to treatment than those who were not diagnosed through screening.…”
mentioning
confidence: 54%